2010
DOI: 10.1176/appi.ps.61.8.774
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Interventions for Adults With Serious Mental Illness: A Systematic Literature Review

Abstract: Objective The promotion of healthy lifestyles among persons with serious mental illness is an integral part of their recovery. The aims of this systematic literature review were to rate the methodological quality of lifestyle intervention outcome studies for persons with serious mental illness, summarize intervention strategies, examine physical health outcomes, and evaluate the inclusion of racial and ethnic minority groups in these studies. Methods Electronic bibliographic database searches were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 26 publications
2
21
0
1
Order By: Relevance
“…A recent systematic literature review of lifestyle interventions for adults with SMI indicated that physical activity (PA) and healthy eating have potential benefit in addressing obesity among individuals with SMI (Cabassa, Ezell, & Lewis-Fernandez, 2010). Specifically, the importance of PA should be emphasized because (1) many forms of PA, such as walking, have been reported to improve physical health (e.g., decreased body fat, improved metabolic risk profiles, and improved physical fitness; Bravata et al, 2007;Daumit et al, 2005; I. M. Lee & Skerrett, 2001) and (2) it can be integrated into peoples' daily lives (Callaghan, 2004;Strassnig, Brar, & Ganguli, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic literature review of lifestyle interventions for adults with SMI indicated that physical activity (PA) and healthy eating have potential benefit in addressing obesity among individuals with SMI (Cabassa, Ezell, & Lewis-Fernandez, 2010). Specifically, the importance of PA should be emphasized because (1) many forms of PA, such as walking, have been reported to improve physical health (e.g., decreased body fat, improved metabolic risk profiles, and improved physical fitness; Bravata et al, 2007;Daumit et al, 2005; I. M. Lee & Skerrett, 2001) and (2) it can be integrated into peoples' daily lives (Callaghan, 2004;Strassnig, Brar, & Ganguli, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As a key contributor to recovery, the pursuit of active living (Cabassa, Ezell, & Lewis-Fernández, 2010;Richardson, Faulkner, 148 Y. Iwasaki et al McDevitt, et al, 2005) has been discussed in relation to counteracting inactive, sedentary lifestyles, and obesity among people with mental illness that present substantial health risks including diabetes and heart disease (Brown, Leith, Dickerson, et al, 2010;Galletly & Murray, 2009;Wheeler, Harrison, Mohini, et al, 2010). However, it is plausible that recovery, in addition to health promotion, may also be strengthened in persons with serious mental illness if efforts to promote active living include enjoyable, expressive, and meaningful leisure experiences (Fullagar, 2008, pp.…”
mentioning
confidence: 99%
“…Reviews of research on lifestyle intervention studies for adults with serious mental illness have found that programs show significant, but modest, effects on weight loss and reducing risk factors for metabolic syndrome (Cabassa, Ezell, & Lewis-Fernández, 2010; Faulkner, Soundy, & Lloyd, 2003). For example, few studies have reported an average weight loss of 5% or more of body weight (Verhaeghe, De Maeseneer, Maes, Van Heeringen, & Annemans, 2011), the minimum amount of weight loss considered necessary to reduce risk of serious health problems (Faulkner et al, 2003).…”
mentioning
confidence: 99%